Solve for k k/11=-3

Math
k11=-3
Multiply both sides of the equation by 11.
11⋅k11=11⋅-3
Simplify both sides of the equation.
Tap for more steps…
Cancel the common factor of 11.
Tap for more steps…
Cancel the common factor.
11⋅k11=11⋅-3
Rewrite the expression.
k=11⋅-3
k=11⋅-3
Multiply 11 by -3.
k=-33
k=-33
Solve for k k/11=-3

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top